2015
DOI: 10.2174/1389450116666150630110821
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Myocardial Homeostasis, Self-Regeneration and Senescence

Abstract: The adult myocardium has limited capacity to preserve, renew or rejuvenate itself. The local microenvironment may induce epigenetic changes affecting the survival, proliferation, function and senescence of cardiac cells at rest and following the exposure to different stressors. The cellular response to microenvironment is characterized by the release of ions, oxygen free radicals, auto/paracrine factors and RNAs that drive the magnitude of gene reprogramming through the interaction with specific promoters. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…Interestingly, we have demonstrated that porcine aortic endothelial cells co-cultured with porcine adipose-derived mesenchymal stem cells (MSCs) under normoxic conditions release increasing amount of exosomes delivering hypoxiainducible factor 1-alpha (HIF1-alpha), in a time dependentmanner [71]. The exosomal release was directly related to the accumulation of free radicals into the culture medium.…”
Section: Cardiac Exosomesmentioning
confidence: 99%
“…Interestingly, we have demonstrated that porcine aortic endothelial cells co-cultured with porcine adipose-derived mesenchymal stem cells (MSCs) under normoxic conditions release increasing amount of exosomes delivering hypoxiainducible factor 1-alpha (HIF1-alpha), in a time dependentmanner [71]. The exosomal release was directly related to the accumulation of free radicals into the culture medium.…”
Section: Cardiac Exosomesmentioning
confidence: 99%
“…DNA methylation refers mainly to the addition of a methyl group to the 5-position of cytosine of CpG sequence of promoter regulatory regions through selective enzymes [5]. The cells use DNA methylation to lock gene trascription in the off position by three mechanisms: i) the blocking of recruitment of transcription factors to correspondent cis-DNA binding elements by steric hindrance, ii) the specific co-binding of proteins to methylated DNA that compete with the specific transcriptional factors [53] and iii) the recruitment of histone deacetylases (HDACs) to silence gene expression [54].…”
Section: Epigenetic Modulation Of Cardioprotectionmentioning
confidence: 99%
“…Histone modifications alter the gene expression through changes in the nucleosome conformation in ). Histones undergo to different posttranslational modifications at level of lysine (acetylation, ubiquitination, methylation, sumolyation) or arginine (methylation) or serine and threonine (phosphorylation) residues [5]. Reversible histone acetylation plays a key role in the development of postischemic myocardial remodelling.…”
Section: Epigenetic Modulation Of Cardioprotectionmentioning
confidence: 99%
See 2 more Smart Citations